STUDY ON METABOLIC PROFILE OF REPEAT BREEDER, POST PARTUM ANESTROUS AND NORMAL CYCLIC SAHIWAL COWS - AGRAWAL, JITENDRA KUMAR; SAXENA, ATUL; SINGH, VIJAY (The Indian Journal of Animal Reproduction, 2023)
This study was conducted with the aim to investigate comparative metabolic profile of repeat breeder,post partum anestrous and normal cyclic Sahiwal cows. A total of 18 Sahiwal Cows having body weight 300 to400 kg, second to fifth lactation and age between four to nine years, were divided into three groups (NormalCyclic, Repeat breeder and Anestrous); each group comprised of 06 animals. Blood samples were collectedaseptically and serum was separated by centrifugation at 3000 rpm for 10 minutes to analyze the glucose (mg/di), total protein (g/dl}, calcium (mg/di), phosphorus (mg/di). The results of present study revealed that serumglucose level of normal cyclic cows was significantly higher than post partum anestrous animals. The normalcyclic animals also had significantly higher calcium and phosphorus level as compared to the anestrous andrepeat breeder animals. These results indicate that higher incidence of repeat breeding and anoestrous inSahiwal cows has been attributed to a decrease in circulation of glucose, total protein, calcium and phosphorus.
Keywords: Anestrous; Repeat breeder; Glucose; Total Protein; Calcium; Phosphorus